2015
DOI: 10.1002/2014jb011015
|View full text |Cite
|
Sign up to set email alerts
|

Medieval pulse of great earthquakes in the central Himalaya: Viewing past activities on the frontal thrust

Abstract: The Himalaya has experienced three great earthquakes during the last century-1934 Nepal-Bihar,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 44 publications
(95 reference statements)
0
45
0
Order By: Relevance
“…1a). This region has not experienced any great magnitude earthquake since 1344 event (Kumahara and Jayangondaperumal 2013;Rajendran et al 2015;Malik et al 2016) or probably the event has not been precisely documented in historical chronicles. Few large magnitude earthquakes 6.6 ≥ Mw ≤ 7.8 have occurred in this region such as 1991 Uttarkashi earthquake Mw 6.9, 1999 Chamoli earthquake Mw 6.6, 1803 Mw 7.2 in Central Himalaya, and 1833 Mw 7.8 with an epicenter in the inferred rupture zone of 1934 Bihar-Nepal earthquake (Bilham 1995) (Fig.…”
Section: Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…1a). This region has not experienced any great magnitude earthquake since 1344 event (Kumahara and Jayangondaperumal 2013;Rajendran et al 2015;Malik et al 2016) or probably the event has not been precisely documented in historical chronicles. Few large magnitude earthquakes 6.6 ≥ Mw ≤ 7.8 have occurred in this region such as 1991 Uttarkashi earthquake Mw 6.9, 1999 Chamoli earthquake Mw 6.6, 1803 Mw 7.2 in Central Himalaya, and 1833 Mw 7.8 with an epicenter in the inferred rupture zone of 1934 Bihar-Nepal earthquake (Bilham 1995) (Fig.…”
Section: Seismicitymentioning
confidence: 99%
“…Trench excavation across Kaladungi Fault-a branching out fault from HFT-suggested that Event I occurred between 467 BC and 570 AD; Event II between 1294 and 1587 AD, and Event III, the Most Recent Event between 1750 and 1932 AD . Another trench excavation at Belparao village near Ramnagar across 13 m high scarp suggested that the slip along the faults in the trench is due to two earthquakes (Rajendran et al 2015). They suggested that an older event around 1050-1259 AD and the younger event around 1259-1433 AD (Rajendran et al 2015).…”
Section: Central Himalaya Ramnagar Sectormentioning
confidence: 99%
“…The MHT fault emerges at the surface along the front of the Himalayan foothills (e.g., Avouac 2003;Ader et al 2012). The MFT dips about 30°(e.g., Rajendran et al 2015) and the MBT about 60°-90°(e.g., Ni and Barazangi 1984). Both of them appear to merge with the MHT at depth-the plane of detachment, commonly referred to as the décollement (Fig.…”
Section: Tectonics and Setting Of Receiver Faultsmentioning
confidence: 99%
“…Over the last decade several teams have worked on the Indian and Nepal parts of the central Himalaya to gain insights into its earthquake generation capabilities. Historical data from the central Himalaya suggest damaging earthquakes in AD 1255, 1344, 698 C P Rajendran 1408, 1505, 1803, and 1833, although their sources and magnitudes remain debated (Rajendran et al, 2015) present new evidence for a great earthquake from a trench across the base of a 13-m high scarp near Ramnagar at the Himalayan Frontal Thrust. Age data suggest that the last great earthquake in the central Himalaya most likely occurred between AD 1259 and 1433.…”
Section: Research Activities During 2010-2016mentioning
confidence: 99%